Effect of the fluorination technique on the surface-fluorination patterning of double-walled carbon nanotubes - Bulusheva, Lyubov G.; Fedoseeva, Yuliya V.; Flahaut, Emmanuel; Rio, Jérémy; Ewels, Christopher P.; Koroteev, Victor O.; Van Lier, Gregory; Vyalikh, Denis V.; Okotrub, Alexander V. (Beilstein Journal of Nanotechnology, 2017)
Double-walled carbon nanotubes (DWCNTs) are fluorinated using (1) fluorine F2 at 200 °C, (2) gaseous BrF3 at room temperature, and (3) CF4 radio-frequency plasma functionalization. These have been comparatively studied using transmission electron microscopy and infrared, Raman, X-ray photoelectron, and near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. A formation of covalent C–F bonds and a considerable reduction in the intensity of radial breathing modes from the outer shells of DWCNTs are observed for all samples. Differences in the electronic state of fluorine and the C–F vibrations for three kinds of the fluorinated DWCNTs are attributed to distinct local surroundings of the attached fluorine atoms. Possible fluorine patterns realized through a certain fluorination technique are revealed from comparison of experimental NEXAFS F K-edge spectra with quantum-chemical calculations of various models. It is proposed that fluorination with F2 and BrF3 produces small fully fluorinated areas and short fluorinated chains, respectively, while the treatment with CF4 plasma results in various attached species, including single or paired fluorine atoms and –CF3 groups. The results demonstrate a possibility of different patterning of carbon surfaces through choosing the fluorination method.
Keywords: double-walled carbon nanotubes; fluorination; NEXAFS; quantum-chemical modeling